Analysis of genes controlling photoperiod sensitivity in common bean using DNA markers - Gu, WK; Zhu, JQ; Wallace, D.H.; Singh, Shree P.; Weeden, N (Springer, 1998)
The genetic basis of the photoperiod response in common bean (Phaseolus vulgaris L.) was investigated using DNA markers and recombinant inbred populations. Two loci affecting photoperiod response were resolved, the previously defined primary locus (Ppd), at which the dominant allele confers sensitivity to photoperiod, and a second locus (herein defined as Hr), which influences the degree to which a plant responds to photoperiod. The DNA marker P51600 cosegregated with the recessive allele, ppd, displaying a recombination frequency with the photoperiod locus of about 3%. A second marker, B303600, was linked to the recessive allele at Hr and mapped approximately 13 cM from this locus. The markers demonstrated that in crosses involving Redkloud and several photoperiod sensitive lines, insensitivity to photoperiod is primarily controlled by ppd and that Hr does not significantly affect flowering time in ppd/ppd plants under the environmental conditions used.